Painful Lesions in an HIV-1 Seropositive African Woman. - Di Bella, Stefano; Taglietti, Fabrizio; Petrosillo, Nicola (Journal of Clinical Research In HIV AIDS And Prevention, 2015)
A clinical case of painful mucocutaneous lesions in an HIV‑1 seropositive woman is presented. The report discusses differential diagnosis, diagnostic work‑up in resource‑limited settings, and targeted therapy considerations.
Keywords: HIV-1; mucocutaneous lesions; differential diagnosis; resource-limited settings